1998
DOI: 10.1111/j.1398-9995.1998.tb03795.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of granule proteins from human eosinophils stimulated with mast‐cell mediators

Abstract: Of mast-cell mediators, LTB4 and PAF induced eosinophil degranulation. The contribution of LTB4 and PAF from mast cells to eosinophil degranulation may be important in the pathogenesis of allergic inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Hence, eotaxin could serve as an end-point chemoattractant also causing degranulation of eosinophils [30]. Notably, PGD 2 and 5-oxo-ETE do not induce eosinophil degranulation [22,42]. Our present data indicate that the complex interplay of chemoattractants at consecutively up-and down-modulating the cells' responsiveness to each other might orchestrate the locomotion of eosinophils over a considerably wide distance, e.g., from the blood stream into the epithelium and alveolar lumen.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, eotaxin could serve as an end-point chemoattractant also causing degranulation of eosinophils [30]. Notably, PGD 2 and 5-oxo-ETE do not induce eosinophil degranulation [22,42]. Our present data indicate that the complex interplay of chemoattractants at consecutively up-and down-modulating the cells' responsiveness to each other might orchestrate the locomotion of eosinophils over a considerably wide distance, e.g., from the blood stream into the epithelium and alveolar lumen.…”
Section: Discussionmentioning
confidence: 99%
“…Chymase, a mast cell-specific protease, and PAF can also regulate eosinophil infiltration, activation and degranulation [54,55]. Tryptase, the other mast cell preformed neutral protease, is capable as well of activating and degranulating eosinophils through binding to the protease-activated receptor PAR2 on eosinophils [28,56].…”
Section: Mast Cells and Eosinophils The Two Components Of ''The Allementioning
confidence: 99%
“…It has been reported that PGD 2 not only increases cytosolic calcium in eosinophils [1]but also primes eosinophils for enhanced release of LTC 4 in response to the calcium ionophore A23187 [2]. In this study, PGD 2 induced ECP release in IL-3-primed eosinophils.…”
Section: Resultsmentioning
confidence: 52%
“…Human eosinophils were purified from venous blood of informed healthy volunteers by 2-step density centrifugation plus negative selection as described previously [1]. Seratrodast was the kind gift from Takeda Pharmaceuticals Co. (Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation